Pelestarian Lingkungan Berbasis Kepercayaan Lokal dan Upacara Tradisi: Studi Kasus Masyarakat di Sekitar Gunung Salak - Royyani, Mohammad Fathi; Walujo, Eko Baroto (Perhimpunan Biologi Indonesia, 2012)
Mount Salak in West Java has important position as water catcment area of water, rain forest, and bank of biodiversity. To protect and conserve this area, Indonesian goverment through the Forest Department develop has Mount Salak to be National Park. Local people who live surrounding Mount Salak have local wisdoms about the benefit of plant and local perspective to manage biodiversity. For local people, Mount Salak is not only to their daily needs but also to save their history and legend about their ancestor. To collect data, we conducted indepth interview with local peple, observed and involved with their ritual local people of Mount Salak have ritual tradition and local belief about Mount Salak, that keep Mount Salak area protected and conserved sustainability.Keywords: Biodiversity, Gunung Salak, Kepercayaan Lokal, Konservasi, Upacara tradisi,